Predicting integrated biology-technical-vocational skills through self-regulation in career-oriented pedagogy - Honra, Joelash R.; Monterola, Sheryl Lyn C.; Yangco, Rosanelia T. (Intelektual Pustaka Media Utama, 2025)
This study addresses the critical issue of enhancing students’ integrated biology-technical-vocational skills, essential for career readiness, by investigating the predictive role of self-regulation within a career-oriented pedagogical framework. Self-regulation, encompassing decision-making, goal orientation, impulse control, and self-direction, is recognized as vital for both academic achievement and career preparedness. Despite its importance, there is a gap in the literature regarding its influence on the development of integrated skills. To bridge this gap, the study employs a quasi-experimental design, utilizing analysis of variance (ANOVA) and simple linear regression on data from a representative sample. The findings reveal that self-regulation significantly predicts the acquisition of these integrated skills. The study concludes that enhancing self-regulation through targeted educational interventions is crucial for fostering students’ career-oriented skills. These insights contribute to educational psychology by highlighting the importance of self-regulation in skill development, offering practical implications for improving academic and vocational outcomes. Future research should further explore these relationships and their practical applications in educational settings.